Amasya-Taşova-Alparslan Beldesi Seyyid Nureddin Alparslan Er-Rufai'nin 655 H. / 1257 M. Tarihli Arapça Vakfiyesi Tercümesi ile 996 H. /1588 M. Tarihli Seyyid Fettah Veli Silsile-namesi - Bayram, Sadi (Vakıflar Genel Müdürlüğü, 1994)
[No Abstract Available]